The effect of six weeks of high-intensity interval training with and without zinc supplementation on aerobic power and anaerobic power in female futsal players - Saeedy, M.; Bijeh, N.; Moazzami, M. (International Journal of Applied Exercise Physiology, 2016)
Purpose: Different training methods and various supplementations are usually used by the athletes to improve their exercise performance. The aim of this study was to investigate the effect of six weeks of HIT with and without zinc supplementation on aerobic and anaerobic power in female futsal players. Methods: Thirty-two female futsal players were randomly divided into 4 groups as placebo, Zinc, HIT and Zinc+HIT. All subjects had to attend futsal-specific training 3 sessions per week. Zinc groups and Placebo group took 30 mg day-1 of zinc gluconate or dextrose, respectively, and HIT groups performed 6-10 repetitions of a 30-second running at 100% of VO2peak with 4 minutes rest between repeats during six weeks. Results: decreased VO2max in placebo group was not significant (P=0.54), however VO2max increased 4.43%, 3.69 % and 9.33% in Zinc, HIT and Zinc+HIT groups, respectively. MPO also augmented 7.84%, 8.78%, 30.85% as well as 11.92% in Placebo, Zinc, HIT and Zinc+HIT groups, respectively. Conclusions: The findings suggest that increased number of futsal training sessions per week, solely ameliorated MPO value; while, Zinc, HIT and HIT along with Zinc supplementation increased both aerobic and anaerobic power in female futsal players after six weeks. It seems that zinc improved the exercise performance because of its utile effect on protein synthesis, muscle tissue development and enzymes activities. Consequently, both of HIT and Zinc supplementation were confirmed as the effective ways to improve exercise performance.